2001
DOI: 10.4049/jimmunol.167.6.3354
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylations at Asn26 and Asn114 of Human MD-2 Are Required for Toll-Like Receptor 4-Mediated Activation of NF-κB by Lipopolysaccharide

Abstract: MD-2 is physically associated with Toll-like receptor 4 (TLR4) and is required for TLR4-mediated LPS signaling. Western blotting analysis revealed the presence of three forms of human (h)MD-2 with different electrophoretic mobilities. After N-glycosidase treatment of the cellular extract prepared from cells expressing hMD-2, only a single form with the fastest mobility was detected. Mutation of either one of two potential glycosylation sites (Asn26 and Asn114) of MD-2 resulted in the disappearance of the slowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 37 publications
1
62
1
Order By: Relevance
“…In a previous study, substitution of Ala for the Asn residue at position 26 at the first glycosylation site of MD-2 did not affect its function, and substitution at the second site, Asn 114 , only caused a minor modification. Considerable reduction in LPS signaling was observed for dual mutations at the Asn residues, but LPS binding was not affected (34). Recently, Visintin et al (27) reported that recombinant soluble MD-1 expressed in mammalian system that contained oligosaccharide chains also did not bind to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, substitution of Ala for the Asn residue at position 26 at the first glycosylation site of MD-2 did not affect its function, and substitution at the second site, Asn 114 , only caused a minor modification. Considerable reduction in LPS signaling was observed for dual mutations at the Asn residues, but LPS binding was not affected (34). Recently, Visintin et al (27) reported that recombinant soluble MD-1 expressed in mammalian system that contained oligosaccharide chains also did not bind to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…MD-2 undergoes N-linked glycosylations at Asn 26 and Asn 114 that are essential for TLR4-mediated activation of NF-B by LPS (48). The calnexin-calreticulin cycle ensures correct folding of proteins that carry monoglycosylated N-linked glycans and retains misfolded conformers in the ER, regulating ER-to-Golgi transport (49).…”
Section: Discussionmentioning
confidence: 99%
“…For activation of the human TLR4/MD-2 receptor complex, the N-glycosylated asparagine residues at positions 26 and 114 of the MD-2 protein are essential (45). In addition to these residues, murine MD-2 is predicted to contain a third glycosylation site at position 150.…”
Section: Analysis Of Chicken Md-2mentioning
confidence: 99%